Business Transformation: Online Sales Application Design Using Laravel: Case Study on One of The Perfume Collection Companies in Bandung - Mardian, Sherli; Komarudin, Komarudin; Fitria, Farhanah; Abdurahman, Fikri Irawan (LPPM STMIK Mardira Indonesia, 2024)
In a progressively sophisticated digital age, e-commerce technology has emerged as an essential element in the commercial landscape. E-commerce allows businesses to access a broader market without geographical constraints and allows consumers to conduct transactions at any time and location. Bossq Parfume Collection functions within the fragrance retail industry. This study used a descriptive methodology. The development methodology is Agile, utilizing system design methodologies based on UML (Unified Modeling Language). The Bossq Parfume Collection has a WhatsApp ordering system that relies on manual documentation, rendering it susceptible to human errors and data loss. Challenges in real-time order monitoring may result in delays in confirmation and shipping, thereby diminishing customer happiness. Moreover, employing Excel for extensive, real-time data management is ineffective, leading to inconsistencies and recording inaccuracies. To resolve these challenges and reduce errors in company administration, we created an application utilizing a PHP framework and JavaScript as programming languages. As a result, we developed an online sales application utilizing the Laravel framework to facilitate effective business management for Bossq Parfume Collection. Adopting an integrated e-commerce system can increase operational efficiency, reduce data management errors, and ultimately promote consumer satisfaction and corporate competitiveness in the digital marketplace.